Review on food insecurity and its relationship with iron and vitamin B12 status among children - Wan Siti Fatimah Wan Abdul Rahman,; Siti Balkis Budin,; Tang, Swee Fong; Poh, Bee Koon (Penerbit Universiti Kebangsaan Malaysia, 2023)
Iron and vitamin B12 are essential micronutrients needed for the growth and development of children. Iron is critical for erythropoiesis, notably in haemoglobin synthesis whereby haemoglobin transports oxygen to cells, which is essential for cellular metabolism and energy production. Meanwhile, vitamin B12 is required for deoxyribonucleic acid synthesis, intracellular metabolism, and blood cells formation and maturation. Lack of these essential micronutrients can lead to nutritional deficiency and anaemia, especially among children. Food insecurity is a condition where there is a lack of or uncertain availability of acquiring acceptable food. Food insecurity is associated with lower nutrient intake and micronutrient deficiencies including iron and vitamin B12, which can subsequently lead to poor health outcomes. Various determinants are associated with iron and vitamin B12 deficiency, and food insecurity, such as socio-economic factors, environmental factors, and dietary intake. This review will explore the possible relationship between iron, vitamin B12, and anaemia with food insecurity among children.